2009
DOI: 10.1007/s11538-009-9468-9
|View full text |Cite
|
Sign up to set email alerts
|

General Model of Inflammation

Abstract: Dysfunctions in the immune system, due to genetics, disease or environmental factors, can cause bacterial colonization and chronic inflammation. In cystic fibrosis and chronic obstructive pulmonary disease, respiratory infections can initiate inflammation of the airway. We propose a system of nonlinear ordinary differential equations to describe interactions between macrophages, both inflammatory and anti-inflammatory cytokines, and bacteria. Small changes in parameters governing inflammatory cytokine producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…The elimination of endotoxin is proportional to the product of the number of activated phagocytic cells and the amount of endotoxin (Asachenkov et al 1994;Copeland et al 2005;Harrison et al 2011;Herald 2010;Loosbroock and Hunter 2014;Reynolds et al 2006;Vedder et al 1999;Zuev et al 2006). Thus, there will be no elimination of endotoxin if there is none of the activated phagocytic cells by this modeling choice.…”
Section: Equation For Endotoxin (P)mentioning
confidence: 99%
“…The elimination of endotoxin is proportional to the product of the number of activated phagocytic cells and the amount of endotoxin (Asachenkov et al 1994;Copeland et al 2005;Harrison et al 2011;Herald 2010;Loosbroock and Hunter 2014;Reynolds et al 2006;Vedder et al 1999;Zuev et al 2006). Thus, there will be no elimination of endotoxin if there is none of the activated phagocytic cells by this modeling choice.…”
Section: Equation For Endotoxin (P)mentioning
confidence: 99%
“…This is a simplification since the anti-inflammatory response is actually recruited by the inflammation. We make this simplifying assumption because the anti-inflammatory response should not be effective against the inflammation until macrophages (part of the pro-inflammatory response) are activated, similar to Herald (2010). This separate activation is the ‘reprogramming’ of already active macrophages by Treg cells.…”
Section: Modelmentioning
confidence: 99%
“…The bacteria component (B) is treated as a growing population that benefits from inflammation—unlike previously mentioned models (Kumar et al , 2004; Reynolds et al , 2006; Herald, 2010) and is reduced by the pro-inflammatory response. We use logistic-type growth since we are not accounting for nutrient for the bacteria to harvest from the body where g is the growth rate.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, T H 1-T H 2-T reg interactions in allergy and immunotherapy follow nonlinear dynamics (Gross et al, 2010). It has been suggested that general models of immune inflammation are most effectively modeled as reflecting nonlinear dynamics (Herald, 2010). In the case of host defense, Joh et al (2009) reported that prediction of disease outbreaks based on the interaction of environmental reservoirs of infectious agents and immune-based host defense follows nonlinear dynamics rather than more conventional linear alterations in equilibrium.…”
Section: Nonlinearity and Chaos Theory In The Immune System And Host mentioning
confidence: 99%